SUNNI: MAKNA, ACUAN DAN RAGAM - Zainul Maarif (UIN Walisongo Semarang, 2018)
Sunni or Sunnism stands for Ahlu As-Sunnah wa al-Jamā`ah which is also called ASWAJA. Many people publish and debate it without clear meaning and reference. This article is a demonstrative-linguistic study that outlines the meaning and reference to the term